Cultural community development center - Quintela, Francis A. (Manila : National University, 2000)
The emergence of nationwide self-awareness and the formation of the concept of a Filipino identity have aroused increasing interest in and concern for tribal Filipinos. There are speculations as to their role in the social as well as economic growth & development of the Philippines. Euphemistically called cultural communities by the government, they are in actually underprivileged Indigenous Inhabitants that include the Manabos in Mindanao, the Mangyans in Mindoro, the Aetas in Zambales, the Tinguias & Igorots in the Cordilleras in the Northern Luzon, to name a few.
Preface -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Review of Related literature -- Chapter III. Research methodology -- Chapter IV. Design framework -- Chapter V. Analysis -- Chapter VI. Summary and Conclusion.
Keywords: COMMUNITY CENTER